The Reimagination of Ch’unhyangjŏn during the Golden Age of Korean Radio Drama : Obal Ch’unhyangjŏn (1964–1965) and Sŏul Ch’unhyangjŏn (1965) - Lee, Eugene (Acta Koreana, 2023)
This study aims to provide an in-depth examination of the radio dramas Obal Ch’unhyangjŏn (誤發 春香傳, 1964–1965) and Sŏul Ch’unhyangjŏn (서울 春香傳, 1965), produced by Tonga Pangsong (DBS) during the 1960s, the golden age of Korean radio drama. The paper will analyze how these radio dramas reflect the contemporary South Korean society, considering their relationship with the classic Ch’unhyangjŏn (春香傳). The dramas followed the style of existing Ch’unhyangjŏn parodies—the cartoon Modŏn Ch’unhyangjŏn (모던 春香傳, 1932–1933) and the novels T’alsŏn Ch’unhyangjŏn (脫線 春香傳, 1951) and Nairon Ch’unhyangjŏn (나이론 春香傳, 1954). Although their titles differ, Obal Ch’unhyangjŏn and Sŏul Ch’unhyangjŏn are the first and second parts of a single work by the dramatist Yi Yongch’an. The former tells the story of Ch’unhyang and Mongnyong from their first meeting to their wedding, whereas the latter continues their story after the wedding. These dramas are particularly noteworthy as they were extremely popular and inspired many more contemporary dramatizations of Korean classics by DBS. Yi retained the narrative structure of the classic Ch’unhyangjŏn and shifted the historical background to the 1960s in an attempt to satirize the contemporary money-dominated South Korean society and provide hope for overcoming it through a new Ch’unhyang figure. Notably, the heroine of his radio dramas is a much more confident and independent figure than the classic Ch’unhyang. These dramas held significance not only as the pioneering modern dramatizations of Ch’unhyangjŏn but also for resonating with the contemporary audience through a modern reinterpretation of this classic literary work.